Evaluation of the groundwater prospective zone by coupling hydro-meteorological and geospatial evidence in Wabe River Catchment Omo Gibe River Basin, Ethiopia - Yonas Mathewos; Brook Abate; Mulugeta Dadi; Markos Mathewos (Water Cycle)
As pressure on groundwater resources continues to increase, zoning the spatiotemporal distribution and occurrence of groundwater potential is critical to ensure sustained water security. Thus, the present study emphasized deciphering the groundwater potential zones of the Wabe River Catchment in the Omo Gibe River Basin, Ethiopia by converging evidence from coupled geographic information systems and remote sensing techniques, aided by the analytical hierarchical process. For this purpose, fourteen predisposing factors of groundwater were conceived. Multicollinearity for each geospatial attribute layer and consistency tests were executed before overlay scrutiny. The obtained result depicted zones with different groundwater prospects such as low (2.65%), moderate (79.24%), high (18.11%), and very high (0.001%) in the river catchment based on weighted overlay analysis. The map removal sensitivity analysis depicted geology and Land use/Land cover as the substantial controlling parameters for the estimate model. The most convincing groundwater potential zones were deciphered in some parts of the catchment along the perennial Wabe River and certain fractured and weathered highly productive aquifers in favorable geological regions. Overall, this study underscored robust sustainable groundwater management with the adaptation of managed aquifer recharge techniques integrated with various watershed management practices to enhance semi-critical and moderate groundwater potential zones in the catchment.